3x+3y+ax+ay=
7a+ab-7x-bx=
2x+2y+abx+aby=
Răspunsuri la întrebare
Răspuns de
2
3x+3y + ax+ay= 3(x+y) +a(x+y)= (x+y)(3+a)
7a+ab - 7x-bx= a(7+b) -x(7+b)= (7+b)(a-x)
2x+2y +abx+aby= 2(x+y)+ ab(x+y)= (x+y)(2+ab)
7a+ab - 7x-bx= a(7+b) -x(7+b)= (7+b)(a-x)
2x+2y +abx+aby= 2(x+y)+ ab(x+y)= (x+y)(2+ab)
Alte întrebări interesante
Limba română,
9 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Biologie,
10 ani în urmă
Limba română,
10 ani în urmă
Biologie,
10 ani în urmă